The first decade of Intervention: facts, figures & trends - Berg, Simon van den; Akello, Grace; Sonpar, Shobna (Intervention, 2013)
This paper aims to explore trends in developments in content and authors’ locations and perspectives in ‘Intervention, the International Journal of Mental Health, Psychosocial Work and Counselling in Areas of Armed Conflict’, from 2003 to 2012. Over this 10 year period, Intervention has published 139 peer reviewed articles, 73 ¢eld reports, 36 book reviews and 33 debate papers.The articles cover academic expertise, practical experience and debates on mental health and psychosocial interventions in the aftermath of both natural, and man made, disasters. The authors of most papers (61%) originated from developed countries, versus 28% from low and middle income countries.Thematic analysis of the content of peer reviewed articles reveals shifting consensus and emerging new debates on mental health and psychosocial interventions. In the first years of Intervention, individual therapeutic approaches were more prominent than in later years, which saw more attention given to community based approaches. Another emerging theme is the trend to involve ‘beneficiaries’ in planning and evaluation of programmes, through participatory approaches. A significant number of peer reviewed papers (28%) describe policy development issues, such as guidelines (IASC) and processes of integration of mental health into general health care systems in post conflict settings. Recommendations are that the editorial priorities for the next years should continue strategies for increasing submissions from authors originating from areas rejected by conflict, and increasing inclusion of perspectives of those who have experienced extreme events.
Keywords: Disaster settings; Post conflict; Practice; Psychosocial intervention; Systematic review; Theory